The Business of Mining: The Mining Business, Uncertainty, Project Variables and Risk, Royalty Agreements, Pricing and Contract Systems, and Accounting for the Extractive Industry - Jones, Odwyn; Lilford, E.; Spearing, S.; Taylor, Grantley (CRC Press, 2018)
The Business of Mining complete set of three Focus books will provide readers with a holistic all-embracing appraisal of the analytical tools available for assessing the economic viability of prospective mines. Each volume has a discrete focus. This first volume presents an overview of the mining business, followed by an analysis of project variables and risk, an overall coverage of the royalty agreements, pricing and contract systems followed by a final chapter on accounting standards and practises for the minerals industry. The books were written primarily for undergraduate applied geologists, mining engineers and extractive metallurgists and those pursuing course-based postgraduate programs in mineral economics. However, the complete series will also be an extremely useful reference text for practicing mining professionals as well as for consultant geologists, mining engineers or primary metallurgists.